Shedding Light on Respiratory Problems in Children with Cerebral Palsy - Pavlina Peneva; Rouzha Pancheva; Silviya P. Nikolova (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Respiratory issues pose significant challenges for children with cerebral palsy (CP). Children with CP often experience complex health challenges that extend beyond their primary condition. Notably, respiratory problems are very common and serious, and even with improvements in healthcare, they are still the main cause of high morbidity and mortality among these children. The purpose of this review is to examine and summarize the most common pulmonary problems in CP children or when CP is a part of another syndrome and to analyze the most common predisposing risk factors for them. This review focuses on the complex factors that affect the breathing of individuals with CP. Repeated lung infections are a major source of problems for this population, highlighting the need to improve their airway health to boost their well-being and lifespan. This review adopted a systematic approach to identify and synthesize recent research on respiratory or pulmonary problems in children, specifically focusing on those with CP. Following the PRISMA guideline, a comprehensive search was conducted across two major scientific databases, PubMed and Scopus, between September 2023 and December 2024. The search utilized combinations of the keywords “cerebral palsy”, “CP”, “pulmonary problems”, “respiratory problems“ “lung problems“ or “pulmonary infections”. No restrictions were imposed regarding the publication date. Eligible studies were required to be original research exploring risk factors influencing respiratory problems in this population, or involving CP children as part of conditions affecting respiratory health. Identifying respiratory illnesses in CP patients can be difficult because their symptoms might be unusual, they may communicate indirectly, testing options can be limited, and getting medical evaluations can be hard. Common risk factors for lung infections include intermittent aspiration, compromised airway clearance, and spinal or chest wall deformities. In addition, nutritive status plays a major role in the results for CP children, with malnutrition being widespread and affecting both their respiratory system and overall well-being. Therefore, an interdisciplinary approach is pivotal to managing these multifaceted issues, challenging the collaboration of specialists and interventions targeting colorful aspects of CP-related respiratory problems. This review emphasizes the significance of early identification, comprehensive evaluation, and acclimatized interventions to improve the respiratory health of CP children. In conclusion, cerebral palsy‘s impact on childhood disability is underscored by its significant influence on respiratory health. Respiratory issues, ranging from aspiration to deformities and compromised function, play a pivotal role in morbidity and mortality. Through collaboration and expertise, this intricate respiratory landscape with precision, empathy, and dedication can be navigated.